DEVELOPING 'KIBAFLO' FLIPBOOK AS CANVA & BOOK CREATOR-BASED INTERACTIVE LEARNING MEDIA FOR 3RD GRADERS ON THE BATTLE OF BADR - Fitri, Alfia Nur; Rahmawati, Revy Trisely; Mariska, Nova; Nur Aeni, Ani (Jurnal Ilmiah Didaktika, 2025)
Digital technology is rapidly advancing, making communication and information access more convenient. This progress is also impacting teaching and learning, making education more efficient and accessible from anywhere. Learning becomes more effective with the appropriate use of learning media. Digital technology helps make learning media more accessible. This study aims to create an interactive digital flipbook titled "KIBAFLO" (Badar Story Flipbook Online). "KIBAFLO" is applied to grade 3 elementary school students. It is created using Canva and Book Creator applications. The flipbook presents Badar War material from the Islamic Religious Education subject effectively and enjoyably. The research method used is descriptive qualitative with a case study approach. The study uses the Design and Development (D&D) approach with the ADDIE model stages. Which includes needs analysis, design, development, implementation, and evaluation. These stages are developed into one integrated whole to produce structured research results.Validation by material and media experts rated the flipbook as 'Very Good'. It is declared feasible and appropriate as a learning medium. The flipbook is expected to increase students' interest, motivation, and understanding. This media also supports better integration of digital technology in education.